Algebra Examples

Solve for m m = square root of 56-m
m=56-m
Step 1
Since the radical is on the right side of the equation, switch the sides so it is on the left side of the equation.
56-m=m
Step 2
To remove the radical on the left side of the equation, square both sides of the equation.
56-m2=m2
Step 3
Simplify each side of the equation.
Tap for more steps...
Step 3.1
Use nax=axn to rewrite 56-m as (56-m)12.
((56-m)12)2=m2
Step 3.2
Simplify the left side.
Tap for more steps...
Step 3.2.1
Simplify ((56-m)12)2.
Tap for more steps...
Step 3.2.1.1
Multiply the exponents in ((56-m)12)2.
Tap for more steps...
Step 3.2.1.1.1
Apply the power rule and multiply exponents, (am)n=amn.
(56-m)122=m2
Step 3.2.1.1.2
Cancel the common factor of 2.
Tap for more steps...
Step 3.2.1.1.2.1
Cancel the common factor.
(56-m)122=m2
Step 3.2.1.1.2.2
Rewrite the expression.
(56-m)1=m2
(56-m)1=m2
(56-m)1=m2
Step 3.2.1.2
Simplify.
56-m=m2
56-m=m2
56-m=m2
56-m=m2
Step 4
Solve for m.
Tap for more steps...
Step 4.1
Subtract m2 from both sides of the equation.
56-m-m2=0
Step 4.2
Factor the left side of the equation.
Tap for more steps...
Step 4.2.1
Factor -1 out of 56-m-m2.
Tap for more steps...
Step 4.2.1.1
Reorder the expression.
Tap for more steps...
Step 4.2.1.1.1
Move 56.
-m-m2+56=0
Step 4.2.1.1.2
Reorder -m and -m2.
-m2-m+56=0
-m2-m+56=0
Step 4.2.1.2
Factor -1 out of -m2.
-(m2)-m+56=0
Step 4.2.1.3
Factor -1 out of -m.
-(m2)-(m)+56=0
Step 4.2.1.4
Rewrite 56 as -1(-56).
-(m2)-(m)-1-56=0
Step 4.2.1.5
Factor -1 out of -(m2)-(m).
-(m2+m)-1-56=0
Step 4.2.1.6
Factor -1 out of -(m2+m)-1(-56).
-(m2+m-56)=0
-(m2+m-56)=0
Step 4.2.2
Factor.
Tap for more steps...
Step 4.2.2.1
Factor m2+m-56 using the AC method.
Tap for more steps...
Step 4.2.2.1.1
Consider the form x2+bx+c. Find a pair of integers whose product is c and whose sum is b. In this case, whose product is -56 and whose sum is 1.
-7,8
Step 4.2.2.1.2
Write the factored form using these integers.
-((m-7)(m+8))=0
-((m-7)(m+8))=0
Step 4.2.2.2
Remove unnecessary parentheses.
-(m-7)(m+8)=0
-(m-7)(m+8)=0
-(m-7)(m+8)=0
Step 4.3
If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.
m-7=0
m+8=0
Step 4.4
Set m-7 equal to 0 and solve for m.
Tap for more steps...
Step 4.4.1
Set m-7 equal to 0.
m-7=0
Step 4.4.2
Add 7 to both sides of the equation.
m=7
m=7
Step 4.5
Set m+8 equal to 0 and solve for m.
Tap for more steps...
Step 4.5.1
Set m+8 equal to 0.
m+8=0
Step 4.5.2
Subtract 8 from both sides of the equation.
m=-8
m=-8
Step 4.6
The final solution is all the values that make -(m-7)(m+8)=0 true.
m=7,-8
m=7,-8
Step 5
Exclude the solutions that do not make m=56-m true.
m=7
(
(
)
)
|
|
[
[
]
]
7
7
8
8
9
9
4
4
5
5
6
6
/
/
^
^
×
×
>
>
1
1
2
2
3
3
-
-
+
+
÷
÷
<
<
π
π
,
,
0
0
.
.
%
%
=
=
 [x2  12  π  xdx ]